ANALISIS PEMASARAN DAN TRANSMISI HARGA PADA PETANI KARET POLA SWADAYA DI DESA JAKE KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Andeska '; Eliza '; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aim is to know and analyze: 1. The channel, margin of rubber marketing and rubber marketing efficiency. 2. The correlation between the price of rubber from factory and the price of rubber in farmer level. 3. The influence of rubber price changing of factory to farmer level at Jake Village of Kuantan Tengah District of Kuantan Singingi Regency. The research method is used of survey method. The sampling method is purposive sampling of 46 farmer that have plantation age between 15-25 years. The second sampling of merchant is using snowball sampling method that come to marketing channel. The research results shows that in Jake Village of Kuantan Tengah District of Kuantan Singingi Regency have one rubber marketing chanel. That is farmer to collector merchant to factory. The lowest price in farmer level is Rp.6.660/kg. The highest price level is Rp. 9.950/kg. The lowest price of factory is Rp. 7.688/kg. The highest price level of factory is Rp. 11.115/kg. The average price level of the farmer level on period April 2013 up to Maret 2014 is Rp. 8.599,42 the average price level on factory is Rp. 9.835,67. The margin level of marketing channel between the price in farmer level and factory is Rp. 1.236,25, marketing eficiency is 6,12%. Correlation value between the price in farmer level and factory level is 0,97%. Value of the elasticity of price transmission between the price received from farmers and the price of bokar by factory was 0,97%. Keywords : Marketing, Margins, Price Transmission, Elasticity.